ANALISIS KEMAMPUAN MENCERMATI TOKOH-TOKOH YANG TERDAPAT PADA TEKS FIKSI SISWA SD MELALUI MODEL SQ3R - Mahmudah, Riyadhotul; Laila, Alfi; Santi, Novi Nitya (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2020)
This article aims to describe: the implementation of the SQ3R model to the ability to examine the characters contained in fiction texts in grade IV students of SDN Ganung Kidul 1 Nganjuk in the 2019/2020 Academic Year. This article is an descriptive qualitative research carried out through five stages, namely: (1) data collection; (2) determination of the sample; (3) recording data; (4) reduction; and (5) drawing conclusions. Data sources in this article are journals and books relating to the learning of the SQ3R model on learning to examine the characters contained in fiction texts. These data provide an overview of the application of the SQ3R model on the ability to examine the characters contained in fictional texts. Furthermore, the object of the research is the learning model SQ3R with a subject of 22 students. The conclusion of the article shows that: this SQ3R model is very good to be applied to the basic competencies of Indonesian language class IV semester II, namely the ability to examine the characters contained in fiction texts.